Alice Adams [videorecording (DVD)] - Stevens, George, 1904-1975; Hepburn, Katharine, 1907-2003; MacMurray, Fred, 1908-1991; Stone, Fred, 1873-1959; McDaniel, Hattie, 1895-1952; Tarkington, Booth, 1869-1946 (Turner Home Entertainment ; Warner Home Video, 2003)
Social climber Alice tries to push her clodhopper family to the background and assumes airs to win the love of an amiable, wealthy young man.